Effect of Ni ion release on the cells in contact with NiTi alloys - Veverkova, Jana; Bartkova, Denisa; Weiser, Adam; Dlouhy, Antonin; Babula, Petr; Stepka, Petr; Pavkova Goldbergova, Monika (Environmental science and pollution research international, 2020)
Nickel-titanium alloys have been used in medical applications for several years; however, biocompatibility of the material remains controversial. In the present study, the human umbilical vein endothelial cells (HUVEC) were cultured in contact with the nitinol used in two different heat treatment surface modifications-helium and hydrogen. The amount of Ni ions released from these alloys in contact with HUVEC was measured in media and in the cells by ICP-MS. An increased release of Ni ions was detected in He alloy compared with H2 alloy modification with an elevation with the metal exposition duration (24 h vs. 72 h). The cells contained the Ni ions in both selected alloy modifications with the lower levels in H2 alloys. To evaluate the potential of multiple metal applications, similar values were observed in media and in cell suspension for all surface modification combinations. The model analysis of effect of metal ion release on distant cells in the body showed that the concentration is interestingly similar to concentrations in cells in direct contact with the metal alloy. The cells are able to regulate the concentration of Ni ions within the cell. According to our best knowledge, the study for the first time describes the presence of Ni ions released from nitinol directly in the cells. In the case of the H2 modification, the lowest levels of Ni ions were detected both in medium and in the cells, which likely increases the biocompatibility of the nitinol alloy.
Keywords: titan; slitiny; ionty; povrchové vlastnosti; Nickel; Ions; lidé; Titanium; Alloys; Endothelial Cells; nikl; Surface Properties; endoteliální buňky; Humans